Insights into the pathophysiology and treatment of amoebic gill disease in Atlantic salmon - Powell, MD; Harris, JO; Melanie Leef; Roberts, SD; Attard, M; Callahan, W; McWilliam, H; Toop, T; Barbara Nowak (2002)
No description available